POLA KONSUMSI PETANI SAWAH DITINJAU DARI HIPOTESIS PENDAPATAN RELATIF TAHUN 1991, DAN TAHUN 1999 (Studi Kasus di Tiga Desa di Kecamatan Sirahpulaupadang) - Kimin, M. Basir (Journal of Indonesian Economy and Business, 2002)
There are 3 selected villages being studied located in Kecamatan Sirahpu laupadang, Kabupaten Ogan Komring Ilir. The inequality of income distribu tion is relatively large. The change of income and neighborâs consumption behavior bring about a significant effect on consumption pattern and level of consumption of a household living adjacent to each other. In addition, there is stability of household or familyâs consumtion pattern and level of con sumption. The peopleâs income level in the three selected villages is deter mined by rice which in turn heavily depends on season, the price of dried rice, and monetary uncertainty. The change of income influence the pattern and level of consumption of the people inderectly in the three villages, and it is not followed by the change of the consumption pattern.Keywords: distribution of income, level of consumption, consumption pattern, elasticity of demand.